Community development projects and their contribution to rural women empowerment in Lulekani of Ba-Phalaborwa Municipality, Limpopo Province - Baloyi, Vongani Olga (My University, 2022)
The implementation of community development projects in rural South Africa was expected, among other outcomes, to empower women by creating opportunities for their sustainable livelihoods. This study investigated contributions made by such development projects on women empowerment in Lulekani of Ba-Phalaborwa Municipality of Limpopo Province. The research objectives were to determine the nature of community development projects, to examine the role of the projects in empowerning women and to find out strategies required to improve the impact of the projects on women empowerment. Anchored within an interpretivist philosophical paradigm, the study employed a qualitative research approach using a case study method. The study population consisted of women who actively participate in community development projects and those who are outside the projects. Purpose sampling was applied in selecting the sample. Inclusion criteria were that participants should have been participating in the projects and/or residing in the community of Lulekani. The sample also included a few women who did not participate in the projects. This was done for comparative purposes. For data collection, unstructured face-to-face and focus group interviews were used. Data were collected about relevant issues on empowerment such as, but not limited to, skills development, income generation, accumulation of assets, social capital and human resource development. The study found that the projects were contributing to women empowerment by creating employment and generating income for them and their families. However, it was evident that much more could be done to multiply the size of incomes and improve their lives of in terms of skills development and by providing support for the long-term sustainability of the projects. The study therefore recommends that policy makers should consider developing to more holistic and appropriate strategies to improve contributions of community development projects on women empowerment. The study concludes that while community development projects have a potential to empower women, this critically depends on strengthening their capacity, particularly with respect to management and administration of those projects as well as enhancing their access to markets and other support.
Thesis (M.Dev. (Planning and Management)) -- University of Limpopo, 2022
Keywords: Community development projects; Rural women empowerment; Lulekani; Ba-Phalaborwa Municipality; Community development -- South Africa -- Limpopo; Community development; Women in rural development; Women in rural development -- South Africa -- Limpopo